KAZAKHSTAN EDUCATION SYSTEM BREAKTHROUGH, HAVING OVERCOME THE TRAGIC EVENTS IN THE HISTORY OF KAZAKH PEOPLE - Л.А., Турумбетовa; Б.М., Мaнaбaев; О.М., Шaяхметов (Journal of Oriental Studies, 2019)
This paper deals with the development of education in Kazakhstan during the historical period from the beginning of the First World War until nowadays, how Kazakh people, having 2% of the population being educated by the time of the October Revolution, came to the present results. The purpose of the study is to show the great changes in the literacy of people, how after one century, in 2017, Kazakhstan ranked the 4th place among 137 countries of the world in terms of primary education according to the Global Competitiveness Index. The author pays much attention to the situation in the country during the twentieth century, the tragic events in the history of Kazakh people. The aim of the author is to give the analysis of the influence of more than seventy years of Soviet power on education, which established a strict order of teaching Russian language in Kazakh schools. The policy of “Russification” of education had an impact on the development of school education in Soviet Kazakhstan. Training of highly qualified scientific experts, engineers of different spheres of industry have become the foundation for the develop- ment of large-scale industrialization nowadays.110 countries in the world consume more than 500 types of products, manufactured in Kazakhstan, though even at the beginning of the XXI century, Kazakhstan was not well known in the globe. It is the evidence of the breakthrough of the new educational model and the model of economic development in the country. Key words: education, population, literacy, approach, transit.